Dampak Kafein Pada Performa Atlet Elit Wanita - Prisca Widiawati; Dinta Sugiarto; Farah Paramita; Muhammad Putra Ramadhan; Yasinda Thasia Audina; Ulma Erdilanita; I Nyoman Sudarmada; Nasnoor Juzaily Nasiruddin (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
Caffeine is one of the most widely consumed ergogenic substances worldwide, with an average daily intake among adults ranging from approximately 100–200 mg/day. In sports contexts, caffeine is commonly used at doses of around 3–6 mg/kg body weight to enhance athletic performance. However, most research on the ergogenic effects of caffeine has primarily focused on male or mixed populations, despite evidence that physiological and hormonal differences may influence female athletes’ responses to caffeine supplementation. This study aimed to systematically review current scientific evidence regarding the effects of caffeine supplementation on the physical and psychophysiological performance of elite female athletes. This study employed a systematic review design in accordance with the PRISMA 2020 guidelines. Literature searches were conducted in the PubMed and Scopus databases for publications from 2016 to 2025. Inclusion criteria were determined using the PICOS framework, focusing on controlled experimental studies involving elite female athletes. Of the 2,254 articles identified, nine studies met the inclusion criteria and were analyzed qualitatively. Most studies used randomized, double-blind, placebo-controlled crossover designs and reported that caffeine supplementation at doses of 2.3–6 mg/kg body weight improved strength, speed, cognitive response, and exercise enjoyment. However, the results were not always consistent, particularly among athletes with high habitual caffeine intake or when lower doses were administered. In conclusion, caffeine may enhance the performance of elite female athletes. Nevertheless, the existing literature presents several limitations, including the limited number of studies, small sample sizes, and variability in study design, caffeine dosage, and control of hormonal factors such as the menstrual cycle. Therefore, caffeine use in female athletes requires a more individualized and gender-specific supplementation approach.